Hand Rejuvenation Using a Combination Approach. (May 2016) - Butterwick, Kimberly; Sadick, Neil
Abstract : BACKGROUND: Hand rejuvenation has been recognized to play a key role in complementing and restoring an overall youthful look. OBJECTIVE: Aging hands present specific characteristics that require a carefully designed combinational treatment for a successful clinical outcome from a practitioner's and patient's perspective. METHODS AND MATERIALS: A Medline search was performed on hand rejuvenation from 1990 to 2015, and results are summarized. The authors' personal experiences with specific technologies are discussed. RESULTS: Review of available clinical studies revealed successful rejuvenation of the epidermis and dermis of the hands with topicals, chemical peels, intense pulsed light, and laser energy devices. Reports of sclerotherapy and laser veins ablation for dorsal hand veins were identified. Several studies on hand volume restoration with injectable volumetric fillers such as hyaluronic acid, calcium hydroxylapatite, poly-L-lactic acid, autologous fat transfer including the authors' personal experience with them are described. CONCLUSION: A plethora of noninvasive treatment options for hand rejuvenation have been thoroughly studied as monotherapy, but there is insufficient number of studies evaluating the best combination of therapies for this indication. It is likely that their strategic combination and sequence of application by a trained clinician will ensure a favorable outcome in addressing patient concerns.